Analisis Hukum Terhadap Putusan Diskriminasi Terhadap PT. Lion Express - Febian Ardi Wirawan; Gregorius Gaby Albert; Dwi Wulan Romadhon; Denise Asha Aliqa; Silvana Fatimatul Zahra (Universitas Sains dan Teknologi Komputer, 2024)
This research aims to conduct a legal analysis of the discriminatory decision against PT. Lion Express. In this context, the study will explore the legal foundations underlying the discriminatory decision and identify its relevance and compliance with applicable legal norms. The research methods include legal document analysis, case studies, and a review of relevant regulations. The results of this research are expected to provide an in-depth understanding of the controversy involving PT. Lion Express and its implications for the legal system. The conclusions drawn from this analysis can assist stakeholders, including legal practitioners and government entities, in formulating legal measures that are fair and in line with principles of justice. This research makes a significant contribution to understanding the legal aspects of corporate discrimination cases and provides a basis for improving a more effective and just legal system.